Hyperglycinuria: diagnosis in middle age. Issue 3 (2nd March 2022) - Fargaly, Hithem; Mathew, Shobi; Rossi, Noreen F
Abstract : Isolated hyperglycinuria is a rare disorder that is associated with osteoporosis and renal calculi. We report findings in a middle-aged, black woman who presented for renal function evaluation with a history of transient hypobicarbonataemia associated with topiramate therapy. She displayed the full triad of high urinary glycine, early-onset osteopenia despite normal reproductive hormones, and renal calculus with high urinary oxalate, phosphate and uric acid. Parathyroid hormone and fibroblast growth factor 23 were both normal. Formal genetic testing did not reveal mutations in SLC6A20, SLC6A18, SLC6A19, SLC36A2, the known genes associated with glycinuria; however, black individuals are poorly represented in the genetic databases. It may well be that otherwise unidentified mutations may be present or that topiramate may result in a lingering proximal tubule defect even after cessation of the drug.